1999
DOI: 10.1093/toxsci/49.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of uranium in rats implanted with depleted uranium pellets

Abstract: During the Persian Gulf War, soldiers were injured with depleted uranium (DU) fragments. To assess the potential health risks associated with chronic exposure to DU, Sprague Dawley rats were surgically implanted with DU pellets at 3 dose levels (low, medium and high). Biologically inert tantalum (Ta) pellets were used as controls. At 1 day and 6, 12, and 18 months after implantation, the rats were euthanized and tissue samples collected. Using kinetic phosphorimetry, uranium levels were measured. As early as 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(109 citation statements)
references
References 31 publications
11
95
2
1
Order By: Relevance
“…Small portions of uranium have also been detected in the lungs and liver (Fulco et al, 2000). Figure 3, as reported by Pellmar et al (1999a), demonstrated the organ distribution of DU following 18 mo of implantation of 4, 10, or 20 DU pellets in SpragueDawley rats. This experiment was repeated using tantalum pellets instead of DU.…”
Section: Distributionsupporting
confidence: 60%
“…Small portions of uranium have also been detected in the lungs and liver (Fulco et al, 2000). Figure 3, as reported by Pellmar et al (1999a), demonstrated the organ distribution of DU following 18 mo of implantation of 4, 10, or 20 DU pellets in SpragueDawley rats. This experiment was repeated using tantalum pellets instead of DU.…”
Section: Distributionsupporting
confidence: 60%
“…The accumulation of U in the hippocampus suggests that U has a direct neurotoxic effect on the central nervous system. It has previously been shown that U may be toxic to this cerebral structure (Pellmar et al, 1999b). Finally, the lack of any significant effect on oxidative stress by exposure to 10 mg.L -1 of U suggests in the context of this study that oxidative stress is not the only causative factor involved in these behavioral disturbances.…”
Section: Discussionmentioning
confidence: 90%
“…For example, it has been shown that U is a developmental toxicant with dose-related fetal toxicity (Arfsten et al, 2001). U crosses the blood-brain barrier (Lemercier et al, 2003) and accumulates in the rat brain after chronic exposure (Pellmar et al, 1999a;Paquet et al, 2006), and several experimental studies have found that it has a toxic effect on the behavior of adult rats (Briner and Murray, 2005;Bellès et al, 2005;Houpert et al, 2005;Lestaevel et al, 2005). This behavioral toxicity is expressed by increased locomotor activity (Briner and Muray, 2005;Bellès et al, 2005), significantly decreased spatial working memory capacities , increased anxiety , and shorter paradoxical sleep .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pellmar et al (27) implanted adult Sprague Dawley rats with up to 20 depleted uranium alloy pellets in the gastrocnemius muscle for 18 months. They noted significantly elevated uranium concentrations in the kidneys, liver, spleen, brain, serum, tibia, skull, and urine at most time points.…”
Section: Effect Of Radionuclide Exposure On Animal Tissuementioning
confidence: 99%